The microbiota of Mozzarella di Bufala Campana PDO cheese: a study across the manufacturing process - Levante, Alessia; Bertani, Gaia; Marrella, Martina; Mucchetti, Germano; Bernini, Valentina; Lazzi, Camilla; Neviani, Erasmo (Frontiers in Microbiology, 2023)
Mozzarella di Bufala Campana PDO cheese (MBC) is a globally esteemed Italian cheese. The traditional cheesemaking process of MBC relies on natural whey starter culture, water buffalo's milk, and the local agroecosystem. In this study, the microbial ecology of intermediate samples of MBC production, coming from two dairies with slightly different cheesemaking technology (dairy M large producer, and dairy C medium-small), was investigated using 16S rRNA amplicon sequencing. This research aimed to provide insights into the dynamics of microbial consortia involved in various cheesemaking steps. All samples, except for raw buffalo milk, exhibited a core microbiome predominantly composed of Streptococcus spp. and Lactobacillus spp., albeit with different ratios between the two genera across the two MBC producers. Notably, the microbiota of the brine from both dairies, analyzed using 16S amplicon sequencing for the first time, was dominated by the Lactobacillus and Streptococcus genera, while only dairy C showed the presence of minor genera such as Pediococcus and Lentilactobacillus. Intriguingly, the final mozzarella samples from both producers displayed an inversion in the dominance of Lactobacillus spp. over Streptococcus spp. in the microbiota compared to curd samples, possibly attributable to the alleviation of thermal stress following the curd stretching step. In conclusion, the different samples from the two production facilities did not exhibit significant differences in terms of the species involved in MBC cheesemaking. This finding confirms that the key role in the MBC cheesemaking process lies with a small-sized microbiome primarily composed of Streptococcus and Lactobacillus spp.